Cortical Morphometric Subclassification of Frontotemporal Lobar Degeneration - Lindberg, O. (AJNR Am J Neuroradiol, 2009)
BACKGROUND AND PURPOSE: Frontotemporal lobar degeneration (FTLD) is a primary neurodegenerative disease comprising 3 clinical subtypes: frontotemporal dementia (FTD), semantic dementia (SD), and progressive nonfluent aphasia (PNFA). The subdivision is primarily based on the characteristic clinical symptoms displayed by each subtype. We hypothesized that these symptoms would be correlated to characteristic patterns of brain atrophy, which could be indentified and used for subclassification of subjects with FTLD. MATERIALS AND METHODS: Volumes of 9 cortical regions were manually parcellated and measured on both hemispheres on 27 controls, 12 patients with FTD, 9 patients with PNFA, and 13 patients with SD. The volumetric data were analyzed by traditional t tests and by a multivariate discriminant analysis (partial least squares discriminant analysis). RESULTS: The ensemble or pattern of atrophy was a good discriminator in pair-wise comparison between the subtypes: FTD compared with SD (sensitivity 100% [12/12], specificity 100% [13/13]); FTD compared with PNFA (sensitivity 92% [11/12], specificity 89% [8/9]); and SD compared with PNFA (sensitivity 86% [11/13], specificity 100% [9/9]). Temporal-versus-frontal atrophy was the most important pattern for discriminating SD from the other 2 subtypes. Right-sided versus left-sided atrophy was the most important pattern for discriminating between subjects with FTD and PNFA. CONCLUSIONS: FTLD subtypes generally display a characteristic pattern of atrophy, which may be considered in diagnosing patients with FTLD.